PENDAPATAN MASYARAKAT DALAM PENGOLAHAN LAHAN TEGAKAN JABON DENGAN SISTEM AGROFORESTRI DI DESA KUALA DUA - Simanjuntak, Tatrina Tatrina; Manurung, Togar Fernando; Roslinda, Emi (JURNAL HUTAN LESTARI, 2023)
Jabon plantation stand covering an area of 3 hectares is a plantation stand owned by PT. Alas Kusuma is processed using an agroforestry system by employees to increase income. Gardening in the Jabon stand is a side business for employees as well as additional income apart from working in a factory. The purpose of this study was to calculate the income of the people of Jabon stand processing with an agroforestry system and analyze the factors that affect the income of land processing with an agroforestry system. The method used is a survey method with interview techniques, with a total of 20 respondents. The calculation of income from agroforestry was analyzed by multiple linear regression. From the results of the analysis, the income received by the land processing community is Rp. 200,000 - Rp. 750,000 per month. The factors that influence the income of agroforestry farmers in Kuala Dua Village are the variables of land area and maintenance costs, while the variables of the number of types of plants, hours of work, and labor wages do not have much effect, with the regression equation of income as follows Y = 91.662 + 2800.305X1 - 9.573X2 - 0.112X3 + 2.066X4 - 0.061X5.Keywords: Agroforestry, Community, Income, Jabon Stand.AbstrakTegakan tanaman Jabon seluas 3 Ha merupakan tegakan tanaman milik PT. Alas Kusuma yang diolah dengan sistem agroforestri oleh para karyawan untuk menambah pendapatan. Berkebun di tegakan jabon merupakan usaha sampingan bagi karyawan sekaligus sebagai penghasilan tambahan selain bekerja di pabrik. Tujuan penelitian ini adalah menghitung pendapatan masyarakat pengolah tegakan jabon dengan sistem agroforestri, menganalisis faktor-faktor yang mempengaruhi pendapatan pengolahan lahan dengan sistem agroforestri. Metode yang digunakan adalah metode survey dengan teknik wawancara, dengan jumlah responden sebanyak 20 orang. Perhitungan pendapatan dari agroforestri dianalisis dengan regresi linier berganda. Dari hasil analisis, pendapatan yang diterima masyarakat pengolah lahan adalah Rp. 200.000 - Rp. 750.000 per bulan. Faktor-faktor yang mempengaruhi pendapatan petani agroforestri di Desa Kuala Dua adalah variabel luas lahan dan biaya pemeliharaan, sedangkan variabel jumlah jenis tanaman, jam kerja, upah tenaga kerja tidak terlalu berpengaruh, dengan persamaan regresi dari pendapatan sebagai berikut : Y = 91,662+ 2800,305X1 - 9,573X2-0,112X3 + 2,066X4-0,061X5.Kata kunci: Agroforestri, Masyarakat, Pendapatan, Tegakan Jabon.